Pengenalan Revolusi Industri 4.0 kepada Remaja - Nur Uddin; Safitri Jaya; Pandu Purwandaru (STKIP Andi Matappa, 2020)
A program for introducing industrial revolution 4.0 to teenager was provided in this community service. The program included seminar and workshop. The seminar gave a general introduction about the industrial revolution 4.0 including the history, technology, challenges, and opportunities. The seminar was followed by a workshop on digital technology applied in the era of industry 4.0. The workshop provided the participants knowledge and experience of robotics and internet of things (IoT) through building WiFi robots. This program was intensively done in 25 hours during five days. The results showed that the program was able to improve the participants’ knowledge and capability in understanding the industrial revolution 4.0 and the basic technology about 60%.